Microbial Community Analysis and Food Safety Practice Survey-Based Hazard Identification and Risk Assessment for Controlled Environment Hydroponic/Aquaponic Farming Systems - Dong, Mengyi; Feng, Hao (Frontiers in Microbiology, 2022)
Hydroponic and aquaponic farming is becoming increasingly popular as a solution to address global food security. Plants in hydroponic systems are grown hydroponically under controlled environments and are considered to have fewer food safety concerns than traditional field farming. However, hydroponics and aquaponics might have very different sources of microbial food safety risks that remain under-examined. In this study, we investigated the microbiomes, microbial hazards, and potential bacterial transmission routes inside two commercial hydroponic and aquaponic farming systems using 16S-ITS-23S rRNA sequencing and a hydroponic food safety practice survey. The hydroponic farming system microbiome was analyzed from the fresh produce, nutrient solution, tools, and farmworkers. Proteobacteria, Actinobacteria, Cyanobacteria, Bacteroidetes, and Firmicutes were the main components of hydroponic/aquaponic farming systems, with Pseudomonas being the most abundant genus in fresh produce samples. We further identified the presence of multiple spoilage bacteria and potential human, plant, and fish pathogens at the subspecies level. Spoilage Pseudomonas spp. and spoilage Clostridium spp. were abundant in the hydroponic microgreen farm and aquaponic lettuce farm, respectively. Moreover, we demonstrated the mapping of Escherichia coli 16s-ITS-23s rRNA sequence reads (∼2,500 bp) to small or large subunit rRNA databases and whole-genome databases to confirm pathogenicity and showed the potential of using 16s-ITS-23s rRNA sequencing for pathogen identification. With the SourceTracker and overlapping amplicon sequence variants, we predicted the bidirectional transmission route between plants and the surrounding environment and constructed the bacteria transmission map, which can be implemented in future food safety risk control plans.